Method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag

By performing multi-step leaching and washing treatment on the electrolytic aluminum overhaul slag, combined with the agitation technology of polyacid solution, the impurity content in battery-grade lithium phosphate was successfully reduced, the problem of high impurity content in the prior art was solved, the battery quality was improved and the process was simplified.

CN119569006APending Publication Date: 2025-03-07HUNAN JIUMO TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510142572.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing electrolytic aluminum overhaul slag synthetic battery-grade lithium phosphate products have high impurities, especially the impurities sulfate and sodium, which affects the quality of the battery.

Method used

After crushing and grinding the electrolytic aluminum overhaul slag, concentrated sulfuric acid, hydrogen peroxide, regulator, strong alkali and strong alkali weak acid salt are added in turn to remove impurities of iron, aluminum, calcium, magnesium, and monovalent ionic solution containing lithium sulfate. Then heat and add sodium phosphate reaction, filter and wash multiple times of water and dilute polyacid solution to remove impurities of sulfate, and finally obtain a lithium phosphate product with a low sodium sulfate content.

Benefits of technology

It effectively reduces the sulfate and sodium impurities content in lithium phosphate products, improves the quality of battery-grade lithium phosphate, simplifies the process flow and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569006A_ABST
    Figure CN119569006A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag, which comprises the following steps: crushing and levigating the electrolytic aluminum overhaul slag to obtain slag powder with preset particle size; sequentially adding a preset amount of concentrated sulfuric acid and alkali into the slag powder to remove iron, aluminum, calcium and magnesium impurities, and filtering to obtain a monovalent ion solution containing lithium sulfate; the method comprises the following steps: heating a monovalent ion solution containing lithium sulfate to 80-100 DEG C, adding a preset amount of sodium phosphate for reaction, and filtering to obtain crude lithium phosphate precipitate and precipitate mother liquor; performing primary pure water stirring washing on the crude lithium phosphate precipitate, then performing dilute polyacid solution stirring washing, finally performing secondary pure water stirring washing, and drying to obtain a lithium phosphate product with low sodium sulfate content; and concentrating and crystallizing the precipitation mother liquor to obtain a sodium sulfate byproduct. The invention aims to remove corresponding impurities in the lithium phosphate product synthesized from the electrolytic aluminum overhaul slag with high cost performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag. Background Art

[0002] At present, in aluminum electrolysis production, in order to improve current efficiency and reduce energy consumption, in addition to adding aluminum fluoride and cryolite, some lithium-containing salts such as fluoride or chloride are usually added to improve the properties of the electrolyte. With the use of lithium-containing fluoride salts, lithium-containing aluminum electrolysis waste slag is produced, and its lithium content is 1% to 2.7% (in terms of Li + (Calculation), and with the increase of existing aluminum production and the increase of aluminum electrolysis waste year by year, how to reasonably recycle and utilize this part of lithium resources will become a way to alleviate the pressure of lithium use brought by the new energy industry, and also reduce the disposal cost of aluminum electrolysis overhaul slag. It can be seen that the synthesis of lithium battery positive electrode materials from overhaul slag is a very economical choice for reducing the cost of lithium batteries and the utilization of electrolytic aluminum waste. Among them, the overhaul slag is leached with sulfuric acid to obtain lithium sulfate leaching solution, and then carbonate or phosphate is used to precipitate lithium to obtain lithium carbonate or lithium phosphate for synthesizing lithium batteries. However, the overhaul slag has a complex composition, and the impurities in its lithium sulfate leaching solution include Na, K, F, Cl, B, Ca, Mg, Al, Fe, etc., and the sulfate in the leaching solution after slag discharge cannot be effectively removed, resulting in a certain mass ratio of sulfate in the subsequent synthesis of lithium carbonate or lithium phosphate products of lithium batteries. When the content of impurities sulfate and sodium is high, it is not conducive to improving the quality of the battery.

[0003] The existing patent publication number CN113387338A discloses a method for producing high-quality battery-grade lithium dihydrogen phosphate products from lithium sulfate. The method uses lithium sulfate solution to add liquid alkali to causticize and then mix with phosphoric acid for precipitation reaction to produce high-quality lithium phosphate, and then use phosphoric acid to hydrolyze into lithium dihydrogen phosphate solution and evaporate to obtain battery-grade lithium dihydrogen phosphate products. However, due to the high impurity content of the prepared lithium phosphate, the battery-grade lithium dihydrogen phosphate impurities sulfate 0.08% and sodium 0.02% content are still relatively high. And the existing patent publication number CN113213445A discloses a method for preparing battery-grade lithium phosphate. The battery-grade lithium phosphate products prepared by this method still have the problem that the impurities sulfate 0.5% and sodium 0.4% content are still very high, which is not conducive to improving the quality of the battery. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag, aiming to solve the technical problem of high impurity content in the existing battery-grade lithium phosphate products synthesized from electrolytic aluminum overhaul slag.

[0005] To achieve the above object, the present invention provides a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag, the method comprising the following steps:

[0006] Step 1, crushing and grinding the electrolytic aluminum overhaul slag to obtain slag powder with a preset particle size;

[0007] Step 2, adding a preset amount of concentrated sulfuric acid, hydrogen peroxide, a regulator, a strong base, and a strong base and weak acid salt to the slag powder in sequence to remove iron, aluminum, calcium, and magnesium impurities, and filtering to obtain a monovalent ion solution containing lithium sulfate;

[0008] Step 3, heating the monovalent ion solution containing lithium sulfate in step 2 to 80-90° C., adding a preset amount of sodium phosphate to react, and filtering to obtain a crude lithium phosphate precipitate and a precipitate mother liquor;

[0009] Step 4, the crude lithium phosphate precipitate in step 3 is firstly subjected to a first pure water stirring and washing to remove impurities dissolved in the water carried by the crude lithium phosphate filtration, and then subjected to a dilute polyacid solution stirring and washing to allow the polyacid solution to repeat the dissolution-recrystallization process with the surface of the lithium phosphate crystal to remove the sodium sulfate impurities wrapped in the lithium phosphate crystal nucleus, and finally subjected to a second pure water stirring and washing to wash away the dissolved sodium sulfate impurities and the residual acid solution, and then dried to obtain a lithium phosphate product with a low sodium sulfate content;

[0010] Step 5, concentrating and crystallizing the precipitated mother liquor in step 3 to obtain sodium sulfate by-product.

[0011] Optionally, in step 3, the monovalent ion solution containing lithium sulfate is heated to 80-100° C. by water bath heating.

[0012] Optionally, in step 3, the molar amount of sodium phosphate added is 2.7 to 3.3 times the molar amount of lithium in the monovalent ion solution containing lithium sulfate.

[0013] Optionally, in step 4, the mass ratio of the crude lithium phosphate precipitate in the first pure water stirring and washing to pure water is 1: (5~10); the mass ratio of the lithium phosphate precipitate after water washing in the dilute polyacid solution stirring and washing to the dilute polyacid solution is 1: (5~10); the mass ratio of the lithium phosphate precipitate after acid washing in the second pure water stirring and washing to pure water is 1: (5~10).

[0014] Optionally, in step 4, the stirring temperature in the first pure water stirring washing, the second pure water stirring washing and the dilute polyacid solution stirring washing are all 60-80° C., and the stirring time is 0.5-1 h.

[0015] Optionally, in step 4, the mass concentration of the dilute polyacid solution is 0.1%-1%.

[0016] Optionally, in step 4, the polyacid solution includes any one of a phosphoric acid solution and a citric acid solution.

[0017] Optionally, the step 2 specifically includes:

[0018] Step 21, adding the slag powder into pure water and mixing and stirring, then heating the water to 70-100° C., and finally adding concentrated sulfuric acid to react for 2-4 hours to fully leach the lithium element, and filtering to obtain a crude lithium sulfate leachate and leached residue, wherein the pH value of the solution after adding concentrated sulfuric acid is controlled to be 2-2.5, and the leachate contains iron and aluminum ions;

[0019] Step 22: heating the crude lithium sulfate leachate obtained in step 21 to 50-70° C., then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions;

[0020] Step 23, adding a strong alkali solution to the filtrate obtained in step 22 to adjust the pH to 10-11, adding a strong base weak acid salt to react, filtering to obtain a monovalent ion solution containing lithium sulfate and calcium-magnesium slag, wherein the molar amount of the strong base weak acid salt is 100-120% of the total molar amount of calcium and magnesium ions.

[0021] Optionally, in step 22, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; and the alkaline oxide includes at least one of calcium oxide and magnesium oxide.

[0022] Optionally, in step 23, the strong alkaline solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.

[0023] Beneficial effects:

[0024] The present invention crushes and grinds the electrolytic aluminum overhaul slag into powder, and then adds concentrated sulfuric acid-alkali in sequence to effectively leach the main elements therein, especially the sufficient leaching of lithium elements, and removes dissolved metal ions, thereby obtaining a monovalent ion solution containing lithium sulfate, and adopts a dilute polyacid solution to stir and wash, which can better remove sulfate in lithium phosphate. At the same time, the dilute polyacid solution can be stirred and washed to remove it well by water, and it will not remain in the lithium phosphate, avoiding the introduction of new impurities. In addition, the removal of sulfate by dilute polyacid solution effectively replaces the existing process of removing sulfate by nanofiltration, extraction, dissolution precipitation, etc. It can be seen that the process flow of removing sulfate adopted in the present invention is simpler, which reduces the cost of removing sulfate from lithium phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1It is a schematic flow chart of an embodiment of a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to the present invention;

[0026] Figure 2 The charge and discharge curves of the button-type half-cell D1 corresponding to Example 1 at different rates (0.1C, 0.2C, 0.5C and 1C);

[0027] Figure 3 : The discharge ratio and cycle number of the button-type half-cell D1 corresponding to Example 1.

[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0029] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0030] See also Figure 1 The present invention provides a schematic flow chart of a method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag, the method comprising the following steps:

[0031] Step 1: crush and grind the electrolytic aluminum overhaul slag to obtain slag powder with a preset particle size. Specifically, the electrolytic aluminum overhaul slag is subjected to graded grinding treatment, that is, the overhaul slag is first coarsely crushed in a crusher, and then ground using a sealed sample making machine, so that the D90 particle size of the slag powder obtained by the graded grinding treatment is less than or equal to 74 μm.

[0032] Step 2: Add preset amounts of concentrated sulfuric acid, hydrogen peroxide, a regulator, a strong base, and a strong base and weak base acid salt to the slag powder in sequence to remove iron, aluminum, calcium, and magnesium impurities, and obtain a monovalent ion solution containing lithium sulfate after filtering.

[0033] Specifically, the step 2 specifically includes:

[0034] Step 21, place the slag powder in a corresponding container and add pure water to mix and stir, then heat the water to 70~100°C, continue to add concentrated sulfuric acid to react for 2~4h, so that the lithium element is fully leached, and filter to obtain crude lithium sulfate leachate and leached slag. Among them, the water heating method is preferably water bath heating, and the pH value of the solution is controlled to be 2~2.5 after adding concentrated sulfuric acid; preferably, the mass fraction of concentrated sulfuric acid is 98%, and the amount of sulfuric acid is 80~120% of the molar amount of all elements in the overhaul slag that can react with sulfuric acid (hereinafter referred to as the theoretical acid consumption molar amount). The control of the above leaching temperature, leaching time and sulfuric acid amount can ultimately ensure that the lithium element is fully leached.

[0035] Step 22, heating the crude lithium sulfate leachate obtained in step 21 to 50-70°C, then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions. The crude lithium sulfate leachate contains iron and aluminum ions, and the molar amount of the added hydrogen peroxide is 1-5 times the molar amount of iron in the leachate, and then the pH value of the solution is adjusted by adding a regulator, the purpose of which is that the alkaline salt and the alkaline oxide neutralize the residual acid of the electrolytic aluminum overhaul slag leachate, and react with iron ions and aluminum ions to generate iron hydroxide and aluminum hydroxide precipitation under weak acid conditions. Preferably, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; the alkaline oxide includes at least one of calcium oxide and magnesium oxide.

[0036] Step 23, adding a strong alkali solution to the filtrate obtained in step 22 to adjust the pH to 10-11, adding a strong base and a weak acid salt to react, and filtering to obtain a monovalent ion solution containing lithium sulfate and calcium and magnesium slag.

[0037] Specifically, by adding a strong alkali solution to adjust the pH, and further adding a strong base weak acid salt to achieve the reaction with calcium and magnesium ions in the filtrate under alkaline conditions to generate magnesium hydroxide, calcium hydroxide, magnesium carbonate, and calcium carbonate precipitates. Preferably, the molar amount of the strong base weak acid salt added is 100-120% of the total molar amount of calcium and magnesium ions; more preferably, the strong alkali solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.

[0038] Step 3, heating the monovalent ion solution containing lithium sulfate in step 2 to 80-100° C., adding a preset amount of sodium phosphate to react, and filtering to obtain a crude lithium phosphate precipitate and a precipitate mother liquor.

[0039] Specifically, the monovalent ion solution containing lithium sulfate is heated to 80-100° C. by water bath heating, and the molar amount of sodium phosphate added is 2.7-3.3 times the molar amount of lithium in the monovalent ion solution containing lithium sulfate. By controlling the amount of sodium phosphate added, most of the lithium in the lithium sulfate solution can be precipitated as lithium phosphate.

[0040] Step 4, the crude lithium phosphate precipitate in step 3 is first washed with pure water for the first time, the purpose of which is to remove impurities dissolved in the water entrained by the crude lithium phosphate filtration. Preferably, the amount of purified water used in the first water washing is 5 to 10 times the mass of the crude lithium phosphate, the washing temperature is 60 to 80° C., and the washing time is 0.5 to 1 h.

[0041] And the dilute polyacid solution is stirred and washed, the purpose of which is to make the polyacid solution and the surface of the lithium phosphate crystal repeat the dissolution-recrystallization process to remove the sodium sulfate impurities wrapped in the lithium phosphate crystal nucleus, that is, the polyacid solution can slightly dissolve the surface of the lithium phosphate crystal, and at the same time, the dissolved lithium ions and phosphate radicals re-form lithium phosphate crystals under the induction of the crystal seeds, thereby achieving repeated dissolution-recrystallization, and releasing the sodium sulfate impurities wrapped in the lithium phosphate crystal nucleus, thereby achieving the purpose of removing sodium sulfate. Preferably, the polyacid solution includes any one of a phosphoric acid solution and a citric acid solution. And the mass concentration of the dilute polyacid solution is 0.1%~1%. And the amount of acid solution used is 5~10 times the mass of lithium phosphate, the stirring and washing temperature is 60~80℃, and the stirring and washing time is 0.5~1h.

[0042] Finally, a second pure water washing is performed to wash away the dissolved sodium sulfate impurities and the residual acid solution, and a lithium phosphate product with a low sodium sulfate content is obtained after drying; preferably, the amount of pure water used for the second washing is 5 to 10 times the mass of the lithium phosphate, the washing temperature is 60 to 80°C, and the washing time is 0.5 to 1h.

[0043] Step 5, concentrating and crystallizing the precipitated mother liquor in step 3 to obtain sodium sulfate by-product.

[0044] The present invention grinds the electrolytic aluminum overhaul slag into powder by graded grinding, and then adds concentrated sulfuric acid and alkali in sequence to effectively leach the main elements therein, especially fully leach the lithium element, and remove the dissolved metal ions, thereby obtaining a monovalent ion solution containing lithium sulfate, and adopts a dilute polyacid solution to stir and wash, so as to better remove sulfate in lithium phosphate. At the same time, the dilute polyacid solution can be stirred and washed to remove the sulfate ions well by water washing, and will not remain in the lithium phosphate, thereby avoiding the introduction of new impurities.

[0045] Further, in order to better illustrate the process and effect of a method for synthesizing lithium phosphate from electrolytic aluminum overhaul slag to reduce sulfate, the following is described in detail through specific examples, the details are as follows:

[0046] Example 1

[0047] Step 1.1, weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing, and grind it with a sealed sample making machine for 2-5 minutes to a slag powder 1 with a particle size less than 200 mesh, the main chemical composition of which is shown in Table 1 below (elements are tested on a dry basis).

[0048] Table 1 Main elements in slag powder

[0049] Step 1.2, take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85°C, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain crude lithium sulfate leaching solution and leaching residue.

[0050] Step 1.3, the crude lithium sulfate leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, calcium oxide is slowly added to adjust the pH to 6.5, the reaction time is 1 hour, and the primary filtrate and iron-aluminum slag are obtained by filtering. Sodium hydroxide is added to the primary filtrate to adjust the pH to 10, an appropriate amount of sodium carbonate is added to react for 1 hour, and a monovalent ion solution mainly containing lithium sulfate is obtained by filtering.

[0051] Step 1.4, the monovalent ion solution containing mainly lithium sulfate in step 1.3 is heated to 85°C, sodium phosphate with a molar amount of 3 times that of Li is added, reacted for 1 hour, and filtered to obtain a crude lithium phosphate precipitate and a precipitate mother liquor. The main chemical composition of the crude lithium phosphate is shown in Table 2 below (elements are tested on a dry basis).

[0052] Table 2 Main chemical components in crude lithium phosphate

[0053] Step 1.5: The crude lithium phosphate precipitate in step 1.4 is stirred and washed with 10 times purified water for 1 hour at a temperature of 80° C. The main chemical composition of the once washed lithium phosphate is shown in Table 3 below (elements are tested on a dry basis).

[0054] Table 3 Main chemical composition of single-wash lithium phosphate

[0055] Step 1.6, the lithium phosphate washed for the first time in step 1.5 is washed twice with 10 times 0.2% dilute phosphoric acid, the washing time is 1 hour, and the washing temperature is 80°C. The main chemical composition of the secondary acid washed lithium phosphate is shown in Table 4 below (elements are tested on a dry basis).

[0056] Table 4-Main chemical composition of secondary pickled lithium phosphate

[0057] Step 1.7, the lithium phosphate acid-washed in step 1.6 is washed with 10 times purified water for a second time, the washing time is 1 hour, the washing temperature is 80°C, and the lithium phosphate product with low sodium sulfate content is dried at 105°C. The main chemical composition of the secondary washed lithium phosphate is shown in Table 5 below (elements are tested on a dry basis).

[0058] Table 5-Main chemical composition of secondary washed lithium phosphate

[0059] Step 1.8, concentrating and crystallizing the precipitated mother liquor in step 1.4 to obtain sodium sulfate as a by-product.

[0060] Example 2

[0061] Step 2.1, weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing, and grind it with a sealed sample making machine for 2-5 minutes to a slag powder 1 with a particle size less than 200 mesh, the main chemical composition of which is shown in Table 6 below (elements are tested on a dry basis).

[0062] Table 6 Main elements in slag powder

[0063] Step 2.2, take 100g of slag powder 1, add it to 200mL of purified water, heat it to 70℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain the crude lithium sulfate leaching solution and leaching slag

[0064] Step 2.3, the crude lithium sulfate leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, calcium oxide and calcium carbonate are slowly added to adjust the pH to 4, the reaction time is 1 hour, and the primary filtrate and iron-aluminum slag are obtained by filtering. Sodium hydroxide is added to the primary filtrate to adjust the pH to 11, an appropriate amount of sodium carbonate is added to react for 1 hour, and a monovalent ion solution mainly containing lithium sulfate is obtained by filtering.

[0065] Step 2.4, the monovalent ion solution containing mainly lithium sulfate in step 2.3 is heated to 80°C, sodium phosphate with a molar amount of 3 times that of Li is added, reacted for 1 hour, and filtered to obtain a crude lithium phosphate precipitate and a precipitate mother liquor. The main chemical composition of the crude lithium phosphate is shown in Table 7 below (elements are tested on a dry basis).

[0066] Table 7 Main chemical components in crude lithium phosphate

[0067] Step 2.5, the crude lithium phosphate precipitate in step 2.4 is stirred and washed with 10 times purified water, the stirring time is 1 hour, and the stirring temperature is 80° C. The main chemical composition of the once washed lithium phosphate is shown in Table 8 below (elements are tested on a dry basis).

[0068] Table 8 Main chemical composition of once washed lithium phosphate

[0069] Step 2.6, the lithium phosphate washed for the first time in step 2.5 is washed twice with 10 times 1% dilute citric acid, the washing time is 1 hour, and the washing temperature is 80° C. The main chemical composition of the secondary acid washed lithium phosphate is shown in Table 9 below (elements are tested on a dry basis).

[0070] Table 9-Main chemical composition of secondary pickled lithium phosphate

[0071] Step 2.7, the lithium phosphate acid-washed in step 2.6 is washed with 10 times purified water for a second time, the washing time is 1 hour, the washing temperature is 80°C, and the lithium phosphate product with low sodium sulfate content is dried at 105°C. The main chemical composition of the secondary washed lithium phosphate is shown in Table 10 below (elements are tested on a dry basis).

[0072] Table 10-Main chemical composition of secondary washed lithium phosphate

[0073] Step 2.8: Concentrate and crystallize the precipitated mother liquor in step 2.4 to obtain sodium sulfate by-product.

[0074] Example 3

[0075] Step 3.1, weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing, and grind it with a sealed sample making machine for 2-5 minutes to a slag powder 1 with a particle size less than 200 mesh. Its main chemical composition is shown in Table 11 below (elements are tested on a dry basis).

[0076] Table 11 Main elements in slag powder

[0077] Step 3.2, take 100g of slag powder 1, add it to 200mL of purified water, heat it to 100℃ and stir, add appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2.5. Filter to obtain crude lithium sulfate leaching solution and leaching slag

[0078] Step 3.3, the crude lithium sulfate leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, calcium oxide is slowly added to adjust the pH to 7, the reaction time is 1 hour, and the primary filtrate and iron-aluminum slag are obtained by filtering. Sodium hydroxide is added to the primary filtrate to adjust the pH to 11, an appropriate amount of sodium carbonate is added to react for 1 hour, and a monovalent ion solution mainly containing lithium sulfate is obtained by filtering.

[0079] Step 3.4, the monovalent ion solution containing mainly lithium sulfate in step 3.3 is heated to 90°C, sodium phosphate with a molar amount of 3 times that of Li is added, reacted for 1 hour, and filtered to obtain a crude lithium phosphate precipitate and a precipitate mother liquor. The main chemical components of the crude lithium phosphate are shown in Table 12 below (elements are tested on a dry basis).

[0080] Table 12 Main chemical components in crude lithium phosphate

[0081] Step 3.5, the crude lithium phosphate precipitate in step 3.4 is stirred and washed with 10 times purified water, the stirring time is 1 hour, and the stirring temperature is 60° C. The main chemical composition of the once washed lithium phosphate is shown in Table 13 below (elements are tested on a dry basis).

[0082] Table 13 Main chemical composition of single-wash lithium phosphate

[0083] Step 3.6, the lithium phosphate washed for the first time in step 3.5 is washed twice with 10 times 0.1% dilute citric acid, the washing time is 1 hour, and the washing temperature is 60° C. The main chemical composition of the secondary acid washed lithium phosphate is shown in Table 14 below (elements are tested on a dry basis).

[0084] Table 14-Main chemical composition of secondary pickled lithium phosphate

[0085] Step 3.7, the lithium phosphate acid-washed in step 3.6 is washed with 10 times purified water for a second time, the washing time is 1 hour, the washing temperature is 60°C, and the lithium phosphate product with low sodium sulfate content is dried at 105°C. The main chemical composition of the secondary washed lithium phosphate is shown in Table 15 below (elements are tested on a dry basis).

[0086] Table 15-Main chemical composition of secondary washed lithium phosphate

[0087] Step 3.8: Concentrate and crystallize the precipitated mother liquor in step 3.4 to obtain sodium sulfate by-product.

[0088] Comparative Example 1

[0089] Step 4.1, weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing, and grind it with a sealed sample making machine for 2-5 minutes to a slag powder 1 with a particle size less than 200 mesh, the main chemical composition of which is shown in Table 16 below (elements are tested on a dry basis).

[0090] Table 16 Main elements in slag powder

[0091] Step 4.2, take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain the crude lithium sulfate leaching solution and leaching slag

[0092] Step 4.3, the crude lithium sulfate leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, calcium oxide and sodium hydroxide are slowly added to adjust the pH to 6.5, the reaction time is 1 hour, and the primary filtrate and iron-aluminum slag are obtained by filtering. Sodium hydroxide is added to the primary filtrate to adjust the pH to 10-11, an appropriate amount of sodium carbonate is added to react for 1 hour, and a monovalent ion solution mainly containing lithium sulfate is obtained by filtering.

[0093] Step 4.4, the monovalent ion solution containing mainly lithium sulfate in step 4.3 is heated to 85°C, sodium phosphate with a molar amount of 3 times that of Li is added, reacted for 1 hour, and filtered to obtain a crude lithium phosphate precipitate and a precipitate mother liquor. The main chemical components of the crude lithium phosphate are shown in Table 17 below (elements are tested on a dry basis).

[0094] Table 17 Main chemical components in crude lithium phosphate

[0095] Step 4.5, the crude lithium phosphate precipitate in step 4.4 is stirred and washed with 10 times purified water, the stirring time is 1 hour, and the stirring temperature is 80° C. The main chemical composition of the once washed lithium phosphate is shown in Table 18 below (elements are tested on a dry basis).

[0096] Table 18 Main chemical composition of single-wash lithium phosphate

[0097] Step 4.6, the lithium phosphate in step 4.5 is washed once with 10 times purified water, the washing time is 1 hour, and the washing temperature is 80° C. The main chemical composition of the twice washed lithium phosphate is shown in Table 19 below (elements are tested on a dry basis).

[0098] Table 19 Main chemical composition of secondary washed lithium phosphate

[0099] Step 4.7, the lithium phosphate acid-washed in step 4.6 is stirred and washed with 10 times purified water for 1 hour at a stirring temperature of 80°C, and dried at 105°C to obtain a lithium phosphate product with a low sodium sulfate content. The main chemical components of the three-washed lithium phosphate are shown in Table 20 below (elements are tested on a dry basis).

[0100] Table 20 Main chemical composition of triple washed lithium phosphate

[0101] Step 4.8, concentrating and crystallizing the precipitated mother liquor in step 4.4 to obtain sodium sulfate by-product.

[0102] Compared with the comparative example 1, the above-mentioned embodiments 1-3 adopt one water washing-washing with a dilute polyacid solution-two water washings. After the two water washings, the S content in the lithium phosphate is reduced to less than 0.21%, while in the comparative example 1, three water washings are adopted to finally obtain the three-water washed lithium phosphate with a S content of 1.95%, which is much higher than the S content in the embodiment, and the polyacid solution will not remain in the lithium phosphate, avoiding the introduction of new impurities.

[0103] The lithium phosphate obtained in the above examples and comparative examples is further made into a positive electrode material and applied in a battery, and the corresponding battery performance is measured.

[0104] Among them, the lithium iron phosphate positive electrode material is prepared by mixing the lithium phosphates A1, A2, and A3 prepared in the above embodiments 1 to 3 with phosphoric acid in a ratio of Li:P of 2:3 to prepare lithium dihydrogen phosphate, which are respectively recorded as B1, B2, and B3.

[0105] B1, B2, and B3 were mixed with a preset amount of ferrous oxalate in a P to Fe mass ratio of 1:1, and sintered at 700°C for 7 hours. The positive electrode materials of lithium iron phosphate batteries were obtained by cooling in the furnace, which were respectively denoted as C1, C2, and C3.

[0106] At the same time, commercially available lithium phosphate was used as raw material to synthesize lithium iron phosphate material through the same process for comparison, which was recorded as C4.

[0107] Preparation of button cells: The prepared lithium iron phosphate positive electrode materials C1, C2, C3, and C4 were used to prepare button cells in the following manner. The prepared button cells were numbered D1, D2, D3, and D4, respectively, and the assembled button cells were subjected to a battery cycle performance test on a blue power test cabinet.

[0108] The preparation process of button half-cell is as follows:

[0109] Under the conventional lithium-ion battery slurry preparation environment (dew point -30°C), lithium iron phosphate positive electrode materials C1-C4, superconducting carbon black (SP) and PVDF binder are mixed in a weight ratio of 8:1:1, and NMP is used as a solvent to make a slurry according to the existing conventional process. Then the above-prepared slurry is coated on aluminum foil and dried to obtain a positive electrode sheet. The negative electrode of the 2032 button half-cell is a metal lithium sheet. The electrolyte uses an EC / DMC (volume ratio of 1:1) solution with a LiPF6 concentration of 1.0 mol / L, and the diaphragm uses a commercial polyolefin diaphragm. The prepared button half-cell was tested on a blue electric test cabinet with a test voltage range of 2.0 to 3.75V and a cycle rate of 1C cycle.

[0110] The lithium phosphate samples A1-A3 prepared by the above embodiments 1-3 and the commercially available lithium phosphate of the comparative example were subjected to electrical cycle performance tests on 2032-type button half-cells D1-D4 prepared by referring to the above method. The test results are shown in Table 21.

[0111] Table 21 - Electrical cycle performance test results of button half-cells D1 to D4

[0112] In order to more intuitively see the rate performance and cycle performance of the button-type battery corresponding to the lithium iron phosphate synthesized from the lithium iron phosphate precursor prepared in the embodiment of the present invention, the performance curve of the corresponding battery D1 is plotted by taking Example 1 as an example. Figure 2 The charge and discharge curves of the button-type half-cell D1 corresponding to Example 1 at different rates (0.1C, 0.2C, 0.5C and 1C) are shown in FIG. Figure 3 The discharge ratio and cycle number of the button-type half-cell D1 corresponding to Example 1 show that the D1 specific capacity of the button-type half-cell finally made from the lithium iron phosphate precursor sample obtained in Example 1 is controlled at about 150 mAh / g, and in the 1C rate cycle diagram, the 300-week cycle retention rate is above 95%. As can be seen from Table 21, the D1-D2 specific capacity of the button-type half-cells in Examples 1-3 is controlled at about 150 mAh / g, and is correspondingly greater than the specific capacity of the commercially available lithium phosphate battery D4 at different rates, and the 1C cycle retention rate of Examples 1-3 can reach more than 98%, which is greater than the 94.6% of the commercially available lithium phosphate battery D4 at 1C cycle retention rate. It can be seen that the lithium iron phosphate positive electrode material prepared by the iron phosphate precursor obtained in the embodiment of the present invention has a higher capacity and a better cycle retention rate and rate performance than the ordinary commercially available lithium iron phosphate precursor.

[0113] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.

[0114] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.

[0115] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag, characterized in that: The method comprises the following steps: Step 1, crushing and grinding the electrolytic aluminum overhaul slag to obtain slag powder with a preset particle size; Step 2, adding a preset amount of concentrated sulfuric acid, hydrogen peroxide, a regulator, a strong base, and a strong base and weak acid salt to the slag powder in sequence to remove iron, aluminum, calcium, and magnesium impurities, and filtering to obtain a monovalent ion solution containing lithium sulfate; Step 3, heating the monovalent ion solution containing lithium sulfate in step 2 to 80-90° C., adding a preset amount of sodium phosphate to react, and filtering to obtain a crude lithium phosphate precipitate and a precipitate mother liquor; Step 4, the crude lithium phosphate precipitate in step 3 is firstly subjected to a first pure water stirring and washing to remove impurities dissolved in the water carried by the crude lithium phosphate filtration, and then subjected to a dilute polyacid solution stirring and washing to allow the polyacid solution to repeat the dissolution-recrystallization process with the surface of the lithium phosphate crystal to remove the sodium sulfate impurities wrapped in the lithium phosphate crystal nucleus, and finally subjected to a second pure water stirring and washing to wash away the dissolved sodium sulfate impurities and the residual acid solution, and then dried to obtain a lithium phosphate product with a low sodium sulfate content; Step 5, concentrating and crystallizing the precipitated mother liquor in step 3 to obtain sodium sulfate by-product.

2. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 1, characterized in that: In step 3, the monovalent ion solution containing lithium sulfate is heated to 80-100° C. by water bath heating.

3. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 1, characterized in that: In step 3, the molar amount of sodium phosphate added is 2.7 to 3.3 times the molar amount of lithium in the monovalent ion solution containing lithium sulfate.

4. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 1, characterized in that: In step 4, the mass ratio of the crude lithium phosphate precipitate to pure water in the first pure water stirring and washing is 1: (5~10); the mass ratio of the lithium phosphate precipitate after water washing to the dilute polyacid solution in the dilute polyacid solution stirring and washing is 1: (5~10); the mass ratio of the lithium phosphate precipitate after acid washing to pure water in the second pure water stirring and washing is 1: (5~10).

5. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 4, characterized in that: In step 4, the washing temperature in the first pure water washing, the second pure water washing and the dilute polyacid solution washing is 60-80° C., and the washing time is 0.5-1 h.

6. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 4, characterized in that: In step 4, the mass concentration of the dilute polyacid solution is 0.1%-1%.

7. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to any one of claims 1 to 6, characterized in that: In step 4, the polyacid solution includes any one of a phosphoric acid solution and a citric acid solution.

8. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag as claimed in claim 7, characterized in that: The step 2 specifically includes: Step 21, adding the slag powder into pure water and mixing and stirring, then heating to 70-100° C., and finally adding concentrated sulfuric acid to react for 2-4 hours to fully leach the lithium element, and filtering to obtain a crude lithium sulfate leachate and leached slag, wherein the pH value of the solution after adding concentrated sulfuric acid is controlled to be 2-2.5, and the leachate contains iron and aluminum ions; Step 22: heating the crude lithium sulfate leachate obtained in step 21 to 50-70° C., then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions; Step 23, adding a strong alkali solution to the filtrate obtained in step 22 to adjust the pH to 10-11, adding a strong base weak acid salt to react, filtering to obtain a monovalent ion solution containing lithium sulfate and calcium-magnesium slag, wherein the molar amount of the strong base weak acid salt is 100-120% of the total molar amount of calcium and magnesium ions.

9. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag as claimed in claim 8, characterized in that: In step 22, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; the alkaline oxide includes at least one of calcium oxide and magnesium oxide.

10. The method for synthesizing battery-grade lithium phosphate from electrolytic aluminum overhaul slag according to claim 8, characterized in that: In step 23, the strong alkaline solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.

Citation Information

Patent Citations

  • Preparation method of battery-grade lithium phosphate

    CN113213445A

  • Method for producing lithium ion battery raw material based on lithium sulfate and lithium sulfate resource utilization process

    CN113387338A

  • Manufacturing method of high purity lithium phosphate from the waste liquid of the exhausted litium-ion battery

    CN106542512A

  • Method for extracting lithium from electrolytic aluminum waste residues

    CN116716487A

  • Method for deeply removing calcium and magnesium

    CN117448572A

Cited By

  • Method for preparing battery-grade lithium phosphate from industrial-grade raw materials

    CN121063497A